A 69-Year-Old Woman with Diabetes Mellitus, Hypertension, Knee Osteoarthritis, Dyslipidemia, and Obesity with Genetic and Lifestyle Factors: A Family Medicine Case Report - Kuntadi, Muhammad (Jurnal Ilmu Kedokteran Keluarga, 2026)
Background: Multimorbidity in older adults is commonly driven by overlapping biological, behavioral, familial, and social determinants. Type 2 diabetes mellitus, hypertension, dyslipidemia, obesity, and knee osteoarthritis frequently coexist through shared mechanisms involving insulin resistance, chronic low-grade inflammation, endothelial dysfunction, oxidative stress, and mechanical joint loading. Case: A 69-year-old woman presented for routine primary care follow-up with bilateral plantar tingling, intermittent occipital headache, and chronic bilateral knee pain. She had been diagnosed with type 2 diabetes mellitus and hypertension since 2016 and later developed dyslipidemia, grade I obesity, symptoms suggestive of diabetic peripheral neuropathy, and bilateral knee osteoarthritis. Her body weight was 69 kg, height 150 cm, and body mass index 30.7 kg/m². Initial blood pressure was 159/80 mmHg and fasting blood glucose was 215 mg/dL. Previous laboratory examination showed HbA1c 9.3%, total cholesterol 201 mg/dL, triglycerides 293 mg/dL, HDL cholesterol 30.5 mg/dL, and LDL cholesterol 106 mg/dL. Family history revealed diabetes mellitus and hypertension in both parents, stroke in paternal relatives, hypertension in her husband and second child, and hypercholesterolemia in two siblings. Intervention and follow-up: Three home visits were conducted on 10 February, 16 February, and 17 April 2025. Interventions included medication adherence education, dietary counseling, family conference, reduction of sweetened beverages, fried foods, organ meats, and fatty foods, activity modification for knee osteoarthritis, and family involvement in symptom, blood pressure, and glucose monitoring. Blood pressure improved from 160/94 mmHg during the first home visit to 135/80 mmHg during the second visit and 138/72 mmHg during the third visit. Random blood glucose decreased from 153 mg/dL to 122 mg/dL and then 110 mg/dL. Tingling improved but persisted, while knee pain during prayer remained functionally relevant. Conclusion: This case illustrates that multimorbidity in older adults cannot be addressed by biomedical treatment alone. A family medicine approach, including family assessment, home visits, behavioral negotiation, and community-oriented follow-up, is essential for improving metabolic control and supporting sustainable lifestyle change.